Anti-proliferative and matrix metalloproteinase-2 inhibition of Longkong (Lansium domesticum) extracts on human mouth epidermal carcinoma - Aranya Manosroi (2018)
Context: Longkong [Lansium domesticum Corr. (Meliaceae)] is a popular tropical plant producing economic edible fruits found mainly in Southeast Asia. However, limited information is available concerning anticancer activity of Longkong. Objective: To investigate anticancer activities in human mouth epidermal carcinoma (KB) of Longkong extracts. Materials and methods: Various parts of Longkong which was collected from Northern and Eastern of Thailand were extracted by the hot and cold processes using water, chloroform, and methanol. The extracts were tested for anti-oxidative activities and anti-proliferation as well as matrix metalloproteinase inhibition on KB cells. Results: The hot water extract of seeds from Northern region (NSEWH), the cold water extract of old leaves from Northern region (NOLWC), and the hot chloroform extract of young leaves from Eastern region (EYLCH) showed the highest free radical scavenging, metal ion chelating, and lipid peroxidation inhibition with SC 50 , MC 50 and IPC 50 values of 0.34 ± 0.03, 0.47 ± 1.60 and 0.86 ± 0.31 mg/ml, respectively. The hot and cold chloroform extract of young fruits from Northern region (NYFCH and NYFCC) exhibited anti-proliferation effect against KB cells with IC 50 values of 603.45 ± 55.35 and 765.06 ± 46.19 mg/ml, respectively. NYFCC exhibited the highest pro- and active MMP-2 inhibition at 53.03 ± 2.65 and 31.30 ± 0.43%, more than all tested standard anticancer drugs except cisplatin. Discussion and conclusion: The cold chloroform extract of young fruits from Northern region appeared to contain anticancer active compounds against KB cells because of its high anti-proliferation and MMP-2 inhibition activities. © 2013 Informa Healthcare USA, Inc. All rights reserved.